(untitled) (Research, Society and Development, 2021)
Nutritional therapy in inflammatory bowel diseases has been consolidated over time as a very effective treatment and based on a diet aimed at tackling these pathologies. The nutritional means used obey well-structured criteria according to the scientific knowledge acquired in the extensive research history of these aspects of the health of ours. The present article, when trying to clarify these benefits, starts from the assumption that the incidence of these diseases is very high and that for their due treatment, a greater range of methodologies is necessary, highlighting which ones stand out as a nutritional therapy. Chronic inflammatory diseases such as inflammatory bowel diseases are classified as of unknown causes. It is believed that they arise from the interaction of four fundamental factors: environmental, genetic, microbial and immunological. These diseases have a great impact on the patient’s quality of life, which is marked by an overload of therapies, hospitalizations and surgeries. Keywords: Nutritional therapy; inflammatory diseases; hospitalizations; surgeries.